Fermentasi Jerami Padi Menggunakan White rot fungi dan Suplementasi Saccharomyces cerevisiae Pengaruhnya terhadap Kecernaan Nutrien Secara In Vitro - Wardhana Suryapratama; Fransisca Maria Suhartati (Jurnal Agripet, 2012)
The influence of rice straw fermentation using white rot fungi and saccharomyces cerevisiae supplementation on in vitro nutrient digestibilityABSTRACT. An experiment to investigate the effect of rice straw fermented using white rot fungi and Saccharomyces cerevisiae supplementation on nutrient digestibility In Vitro had been implemented in two phases. The first experiments undertaken to make rice straw fermentation, using experimental methods with a Completely Randomized Design. As the treatment were White rot fungi (Phanerochaete chrysosporium) 0, 5 and 10 g/kg of rice straw (DM basis). Each treatment was repeated six times, so there are 18 experimental units. The variables measured included nutrient content of rice straw. A second experiment carried out in vitro to test the best rice straw fermentation results of the first experiment, using experimental methods, with a Completely Randomized Design. As the treatment were the supplementation of Saccharomyces cerevisiae (0, 2, 4% of the weight of fermented rice straw, DM basis). The variables measured included digestibility of dry matter, organic matter, cellulose and lignin digestibility of feed containing fermented straw. The data obtained were analyzed using analysis of variance test followed by Orthogonal Polynomials. The results can be concluded that the fermented rice straw using Phanerochaete chrysosporium 10 g/kg of rice straw is the best nutrient content. Saccharomyces cerevisiae supplementation on feed that contains fermented rice straw using Phanerochaete chrysosporium 10 g/kg rice straw is 2%.